SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN KARYAWAN DENGAN METODE AHP TOPSIS (Studi Kasus: PT. Global Retailindo Pratama) - Santika, Putu Praba; Handika, I Putu Susila (SINTECH (Science and Information Technology) Journal, 2019)
To get good employees, a good selection process is needed. From the results of the interview, PT. Global Retailindo Pratama uses four criteria for the selection of new employees, education, intelligence, experience, and interviews. All prospective employees must take an exam to measure the criteria of education and intelligence and also have to send a photocopy of proof of their experience. The first stage selection is done to determine the prospective applicants who will take part in the interview. The second stage is conducted to determine the prospective employees who are accepted. The process of assessment and selection is still done by humans, so it takes a lot of time and energy. This problem can be solved by providing an information system for submitting applications and conducting examinations online. All documents are sent in digital form, also automaticlly checking answers from prospective employees. To select prospective employees, a method is needed that can recommend potential prospective employees based on specified criteria. The TOPSIS method is a decision support method that can provide recommendations in accordance with the criteria. The disadvantage of the TOPSIS method is that it requires weighting in the ranking process. The Analytical Hierarchy Process (AHP) method can be used to determine the criteria weight. Combining AHP and TOPSIS methods can produce more objective ranking results. Combining the AHP and TOPSIS methods can produce better recommendations.